Information disclosure by a seller in a sequential first-price auction - Helmuts Azacis (Cardiff University, Cardiff Business School, 2017)
I study a sequential first-price auction where two items are sold to two bidders with private binary valuations. A seller, prior to the second auction, can publicly disclose some information about the outcome of the first auction. I characterize equilibrium strategies for various disclosure rules when the valuations of bidders are either perfectly positively or perfectly negatively correlated across items. I establish outcome equivalence between di erent disclosure rules. I find that it is optimal for the seller to disclose some information when the valuations are negatively correlated, whereas it is optimal not to disclose any information when the valuations are positively correlated. For most of the parameter values, the seller's revenue is higher if the losing bid is disclosed. When only the winner's identity is disclosed, the equilibrium is efficient whether the valuations are positively or negatively correlated.
Keywords: D44; D47; D82; 330; Efficiency; Information disclosure; Seller's revenue; Sequential first-price auction